Non-linear relationship between urinary creatinine and diabetic kidney disease: implications for clinical practice - Huihong Cao; Li Song; Xiaojun Wang; Haochen Guan (BMC Nephrology)
Abstract Objective This study aims to investigate the relationship between urinary creatinine (UCr) and the risk and severity of Diabetic Kidney Disease (DKD) in patients with Type 2 Diabetes Mellitus (T2DM). The goal is to establish UCr as a potential biomarker for early DKD detection and severity assessment. Methods A retrospective cross-sectional analysis was conducted using medical records of T2DM patients. Patients were classified into groups with and without DKD, and relevant clinical data, including demographic, blood, and urine parameters, were collected. Logistic regression and receiver operating characteristic (ROC) curve analysis evaluated the association between UCr levels and DKD. Curve fitting and threshold effect model were used to further evaluate the relationship between UCr and the incidence and severity of DKD. Results A total of 302 T2DM patients were analyzed, with 137 diagnosed with DKD. Significant differences in clinical parameters were observed between the DKD and non-DKD groups, particularly in UCr, urine albumin levels, and eGFR. UCr levels demonstrated a strong association with DKD. Moreover, a non-linear relationship was identified, with specific inflection points indicating different correlation patterns of UCr with DKD occurrence and progression. Conclusion The findings of this study highlight the potential of UCr as a valuable biomarker for early detection and assessment of DKD in T2DM patients. Incorporating UCr measurements into routine clinical practice could enhance early identification of patients at risk for kidney complications, leading to timely intervention and improved patient outcomes.